IMPLEMENTASI TEKNOLOGI WEB SEMANTIK DALAM APLIKASI PENCARIAN KATALOG ONLINE PERPUSTAKAAN UNIVERSITAS BINA DARMA - Andri, Andri (Universitas Bina Darma, 2013)
Abstract: The online catalog is a catalog of the library system that uses a computer, a catalog can provide a collection of bibliographic information. Catalogs are typically designed to simplify the user. In this research will be made a prototype online library catalog search application that utilizes semantic web technologies. Semantic web technologies allow describing objects and repositories in the form of ontology. Ontology represents semantic levels for knowledge ontology containing semantic entities instead of words. The application was built using JSP (Java Server Page) web based programming. Application of semantic web technologies in the study was able to provide results to the user with the information presented richer. Keywords: Semantic Web,Catalog, JSP